Degradation of Ciprofloxacin by Titanium Dioxide (TiO2) Nanoparticles: Optimization of Conditions, Toxicity, and Degradation Pathway - Mohammad Rofik Usman; Azmi Prasasti; Sovia Islamiah; Alfian Nur Firdaus; Ayu Wanda Marita; Syamsiyatul Fajriyah; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The popular use of ciprofloxacin is often irrational, so it causes environmental pollution such as resistance. The solution to overcome environmental pollution due to ciprofloxacin is degradation by using TiO2 nanoparticles. TiO2 nanoparticles performance is influenced by environment such as light source, pH solvent, duration of lighting and TiO2 nanoparticles mass. The residual levels determination of ciprofloxacin was carried out by using a UV-Vis spectrophotometer. Toxicity test of ciprofloxacin degradation products with TiO2 nanoparticles used Escherichia coli bacteria. Liquid Chromatography Mass Spectrometry (LCMS) was used to determine the type of ciprofloxacin degradation product with TiO2 nanoparticles. The optimum condition for the ciprofloxacin degradation with TiO2 nanoparticles is lighting for 5 hours by using a white mercury UV lamp and 50 mg TiO2 nanoparticles with pH solvent of 5.5. The toxicity of ciprofloxacin degradation product with TiO2 nanoparticles was low. The smallest degradation product identified with m/z was p-fluoraniline (m/z 111). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).